Indonesian navy post and social solidarity influence of Puger fisherman community resilience in facing covid-19 pandemic - Koko Komarudin; Retno Adrianti; Mustain Mashud (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2023)
The role of Indonesian Navy Post (Posal) Puger is very essential, not only as implementing policies to empower marine defense areas, during the Covid 19 pandemic, they were also actively involved in helping to overcome the impact of the Covid 19 pandemic. Covid 19 has an impact on various aspects of life and levels of society, including fishermen. Puger fishermen can survive in carrying out their role in the midst of the Covid 19 pandemic based on good social solidarity. Social solidarity is one of the identities of the fishing community, as well as strengthening resilience in the face of the Covid 19 pandemic. This study aims to analyze the significance of the role of Indonesian Navy Post and social solidarity on the community resilience of the Puger fishing community in dealing with Covid 19. The research approach used is quantitative with method of structural equation modeling (SEM) by testing confirmatory factor analysis and path analysis. The samples taken were 150 respondents from a total population of 10,329 people. The sampling technique used is simple random sampling. The results for each construct show that firstly, the role of Posal has a positive effect on fishermen's resilience (β=0.189 p: 0.067 > 0.05), yet it is less significant due to limited personnel number. Secondly, fishermen social solidarity has a positive effect on fisherman resilience and significance (β= 0.283 p: 0.011 < 0.05) as they involve in various informal activities of fishermen in daily life who help each other in difficulties, care for fellow fishermen and exchange information as well as good cooperation to cope with the current critical conditions.